Effect of Different Parameters on Catalytic Production of Biodiesel from Different Oils. Issue 1 (9th December 2021) - Zaman, Fakhar; Ishaq, Muhammad Waqas; Ul‐Haq, Noaman; Rahman, Wajeeh Ur; Ali, M. Muzaffar; Ahmed, Faisal; Haq, Anwar ul
Abstract: Compared to fossil fuels, renewable fuels (biodiesel) are promising alternatives with similar properties which could reduce the emission of toxic gases and carbon foot print. Biodiesel is mostly used in some developing countries especially in the transportation sector and can be produced from vegetable oils, animal fats, non‐edible oil, and waste cooking oil by different methods. Animal fat and used cooking oil is not feasible for biodiesel production because of numerous problems during production. Catalysts can be selected or synthesized according to the nature of the feedstock. The selection of highly efficient catalysts is necessary to obtain a high yield of biodiesel and their recyclability is also highly important. Different factors affect the transesterification process and analysis of the final biodiesel product is important and necessary to fulfill the requirements of the American Society for Testing Materials (ASTM) standards. In this regard, production of biodiesel from different sustainable and renewable resources could be recommended at industrial level. Further research is required to improve the efficiency. Abstract : Biodiesel as sustainable and renewable alternative to the finite supply of petrodiesel could be used in place of fuel in internal combustion engines. Biodiesel can be produced from different sources such as vegetable oils, animal fats, non‐edible oils, and waste cooking oil. All parameters affecting the biodiesel production process from different sources are reviewed and discussed.